Chlorophyll biosynthesis suppression, oxidative level and cell cycle arrest caused by Ni, Cr and Pb stress in maize exposed to treated soil from the Ferronikel smelter in Drenas, Kosovo - Bekim Gashi; Liridon Buqaj; Ramë Vataj; Metin Tuna (Plant Stress, 2024)
Although certain trace elements are essential for normal plant functionality, an excessive increase in their concentration can disrupt plant development and physiology due to phytotoxicity. This study aims to determine the toxic tolerance limits for different concentrations of Ni and Cr (50, 100, 200, and 400 ppm) and Pb (20, 50, 100, and 200 ppm) in maize seedlings grown in soil collected near the Ferronikel smelter in Drenas, Kosovo. We will assess these limits using sensitive biomarkers, including δ-aminolevulinic acid dehydratase (ALA-D) activity, δ-aminolevulinic acid (ALA) content, chlorophyll content, glutathione (GSH) levels, and lipid peroxidation (MDA), as well as by evaluating DNA content and cell cycle dynamics. All the investigated heavy metals showed a significant increase in concentration in leaves; in particular, Ni showed a strong significant association between its concentration in treatment and in the leaves. At concentrations of 400 ppm, Ni and Cr had significant negative effects on all biomarkers, with ALA-D activity inhibited by up to 50%, and total chlorophyll content significantly decreased. A robust correlation was observed between Ni and Cr and the level of cellular oxidative stress in leaves, as monitored through GSH, lipid peroxidation, and ALA levels. Additionally, the cell cycle, especially in the G1 and G2/M phases, was arrested. These findings emphasize the significant adverse impact of high concentrations of Ni and Cr in plant metabolism. This research contributes to our understanding of managing and mitigating heavy metal contamination in agricultural areas and its potential implications for plant defense mechanisms.